2013
DOI: 10.1101/gad.211912.112
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic binding of RBPJ is determined by Notch signaling status

Abstract: Notch signaling plays crucial roles in mediating cell fate choices in all metazoans largely by specifying the transcriptional output of one cell in response to a neighboring cell. The DNA-binding protein RBPJ is the principle effector of this pathway in mammals and, together with the transcription factor moiety of Notch (NICD), regulates the expression of target genes. The prevalent view presumes that RBPJ statically occupies consensus binding sites while exchanging repressors for activators in response to NIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
236
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(266 citation statements)
references
References 42 publications
18
236
2
Order By: Relevance
“…FIMO (find individual motif occurances) scanning using the generally acknowledged consensus binding motif for RBPJ (41,42) revealed not only scattered binding sites far upstream, but also two distinct clusters, one located 250 bp upstream from the TSS and a smaller one directly at the TSS, supporting direct RBPJ regulation of the ΔN-p63 locus. In addition, analysis using a longer consensus binding motif that enriches for sites of coincident RBPJ/NICD binding (42) predicted two such sites in the more upstream area, consistent with published reports suggesting that in general, NICD/RBPJ binding occurs further away from the TSS, whereas NICD-independent RBPJ binding is more enriched closer to the TSS (Fig.…”
Section: T2mentioning
confidence: 99%
“…FIMO (find individual motif occurances) scanning using the generally acknowledged consensus binding motif for RBPJ (41,42) revealed not only scattered binding sites far upstream, but also two distinct clusters, one located 250 bp upstream from the TSS and a smaller one directly at the TSS, supporting direct RBPJ regulation of the ΔN-p63 locus. In addition, analysis using a longer consensus binding motif that enriches for sites of coincident RBPJ/NICD binding (42) predicted two such sites in the more upstream area, consistent with published reports suggesting that in general, NICD/RBPJ binding occurs further away from the TSS, whereas NICD-independent RBPJ binding is more enriched closer to the TSS (Fig.…”
Section: T2mentioning
confidence: 99%
“…oPossum analysis showed that 1622 out of 2403 Notch dependent open chromatin identified by FAIRE in mK4 cells have a Runx1 motif within 100bp of a RBP motif (Z-score of 176.331). Similarly, "dynamic" RBP ChIPed sites identified in C2C12 cells (Castel et al, 2013) displayed greater labeling by mature complexes than by the N1/RBP immature complex ( Figure S6F). The strength of this approach is demonstrated by the ability of SpDamID to distinguish monomeric from dimeric binding, and detect DNA-bridged DAM complementation when noninteracting factors (Notch and Runx1) bind simultaneously to the same enhancer, a nontrivial tasks with antibody-based methodologies.…”
Section: Mature Notch Complexes Enrich For Dynamic Sites That Open Inmentioning
confidence: 99%
“…It has been observed that some sites in the genome are occupied only when Notch signaling is active ("dynamic sites"; (Bray and Bernard, 2010;Castel et al, 2013;Housden et al, 2013;Krejci et al, 2009;Wang et al, 2014;Wang et al, 2011). These dynamic sites show increased recoverability by RBP ChIP when NICD is present, leading to the proposal that the NICD/RBP complex acts as a pioneer factor to modify chromatin at these sites (Castel et al, 2013).…”
Section: Mature Notch Complexes Enrich For Dynamic Sites That Open Inmentioning
confidence: 99%
See 2 more Smart Citations